1988
DOI: 10.1007/bf00205613
|View full text |Cite
|
Sign up to set email alerts
|

CEA-containing immune complexes in sera of patients with colorectal and breast cancer ? analysis of complexed immunoglobulin classes

Abstract: A sandwich enzyme immunoassay was developed to detect circulating immune complexes containing carcinoembryonic antigen (CEA) and immunoglobulin (Ig) G, IgA, or IgM using a nitrocellulose-bound anti-CEA antibody as the solid phase reagent. Elevated levels of CEA-containing circulating immune complexes (CEA-IC) were found in 15.4% of 117 sera from patients with colorectal cancer in a postsurgery follow-up study. Also in 24.5% of 102 sera from patients with breast cancer in different states of disease CEA-IC were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Most of these assays have been developed for bacterial, viral or allergen antigens. In a few cases, detection of autoantigens as CIC has been proposed to enhance the sensitivity of cancer detection or prognosis monitoring utilizing prostate-specific antigen (PSA), 6 squamous cell carcinoma antigen, 7 carcinoembryonic antigen 8 and CA-125. 9 Thus, autoantigen-antibody complexes have been shown to be useful disease biomarkers, but progress in the discovery of new CICs has been extremely slow.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these assays have been developed for bacterial, viral or allergen antigens. In a few cases, detection of autoantigens as CIC has been proposed to enhance the sensitivity of cancer detection or prognosis monitoring utilizing prostate-specific antigen (PSA), 6 squamous cell carcinoma antigen, 7 carcinoembryonic antigen 8 and CA-125. 9 Thus, autoantigen-antibody complexes have been shown to be useful disease biomarkers, but progress in the discovery of new CICs has been extremely slow.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor antigens associated with immunoglobulins, mainly IgG, can form circulating immune complexes, and this has been reported for few biomarkers, such as carcinoembryonic antigen (CEA) and TA90 for colon cancer,67,68 and MUC-1 or p53 for breast cancer 69. We have recently reported that alfa-fetoprotein (AFP) and squamous cell carcinoma antigen (SCCA) (for liver cancer) and CEA ( for colorectal cancer) could be detected in the serum of patients with cancer, forming complexes with IgM, opening a new gateway for cancer detection 5052…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is no evidence to date on the immunogenicity of CEA. There are no reports in the literature of human T-cell responses to CEA, and there are conflicting reports on whether antibodies to CEA exist or are artifacts [29][30][31][32]. Even if tolerance to CEA does exist, it may be broken by the use of a recombinant CEA vaccinia vaccine (designated rV-CEA).…”
Section: Rationale For Success or Failurementioning
confidence: 99%